Street Naming in the City of Kyzyl (Tuva) - Lamazhaa, Chimiza K.; Markova, Elena A.; Buribayeva, Mainura A. (The New Research of Tuva, 2025)
This article presents a study of street naming policy in Kyzyl, the capital of the Republic of Tuva. The authors analyze a wide variety of urban toponyms, including not only streets but also lanes, squares, avenues, and parks, considering them as components of the city’s hodonymic landscape. The research employs an interdisciplinary approach, integrating philology, linguistic and cultural studies, geography, history, political science, and sociology. The sources for this study include the official database of addressable objects from the Kyzyl City Hall, normative documents issued by city authorities, materials from the National Archives of the Republic of Tuva, as well as local history research and publications in regional mass media. Several street name classification schemes are reviewed. Identified categories include: neutral Russian-language names (44%); anthroponymic names (17.3%); Soviet names (14.7%); toponyms based on Tuvan geographical names (11.3%); heroic (military) names (5.3%); names containing Tuvan words and concepts rooted in Tuvan culture and history (5.4%); toponyms based on place names of the country and world (3.2%); and names referencing personal names (mostly Tuvan) (1.3%). Linguistic classification shows that street names with Russian terms and personal names comprise the majority—73.8%, while those with Tuvan names and terms account for 27.4%. The analysis examines street names through the perspective of significant Russian-Soviet influence, while also noting the emergence of local Tuvan names in recent years. The study highlights the situational nature of street naming policy, which has remained largely unchanged over time. The results make it possible to assess the degree of preservation of ethnic and historical specificity in contemporary urban toponymy of Kyzyl and to identify key trends in the politics of naming urban objects.